The Inhibition of Urokinase by Aromatic Diamidines - Geratz, J. D; Cheng, Michael C.-F (Thrombosis and Haemostasis, 1975)
1. Structure-activity relationships have been established for the inhibition of urokinase by aromatic diamidines. In an assay system employing purified urokinase and human plasminogen the most potent inhibitor was found in 4′,4″-diamidino-2-hydroxy-1,4-diphenoxybutane which proved 5600 times more active on a molar basis than epsilon-aminocaproic acid (E-ACA).2. 4′4″-diamidino-2-hydroxy-1,4-diphenoxybutane behaved as a competitive inhibitor of the urokinase catalyzed hydrolysis of Nα-acetyl-L-lysine methyl ester. At pH 7.85 and 37° C the Ki value was determined as 3.18 × 10–6 M which compares with a value of 6.79 × 10–5 M for p-aminobenzamidine and 3.57 × 10–2 M for E–ACA.3. In two fibrinolytic tests including urokinase as activator the superiority of diamidines over E–ACA was less marked than in the pure plasminogen activation system. This was due to the presence of certain plasma proteins in the fibrinolysis assays which augmented the inhibitory strength of E-ACA. The order of effectiveness of diamidines in the lysis tests was also different from the one in the activation test. In a human fibrin clot lysis test the most active inhibitor was 3′3″-diamidino-2-hydroxy-1,4-diphenoxybutane which was 1700 times more effective on a molar basis than E-ACA. In a human plasma clot lysis test the strongest inhibitor, 2-hydroxy-stilbamidine, was 70 times more powerful than E–ACA.